2022
DOI: 10.3389/ijph.2022.1604468
|View full text |Cite
|
Sign up to set email alerts
|

Financial Loss and Depressive Symptoms in University Students During the First Wave of the COVID-19 Pandemic: Comparison Between 23 Countries

Abstract: Objectives: To assess the association between students’ financial loss and depressive symptoms during the first wave of the coronavirus disease 2019 (COVID-19) pandemic and whether this association varied by countries having different levels of lockdown measures.Methods: This cross-sectional survey, conducted in spring 2020, included 91,871 students from 23 countries. Depressive symptoms were measured using the shortened Center for Epidemiological Studies Depression Scale and information on lockdowns retrieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…29 This is important because financial strain during the pandemic has been linked to depressive symptoms. 18,26 According to the findings of Negash et al, 26 financial strain was significantly associated with depressive symptoms. Unfortunately, in this study, we could not assess whether students experienced financial hardship and whether it was associated with their mental health.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…29 This is important because financial strain during the pandemic has been linked to depressive symptoms. 18,26 According to the findings of Negash et al, 26 financial strain was significantly associated with depressive symptoms. Unfortunately, in this study, we could not assess whether students experienced financial hardship and whether it was associated with their mental health.…”
Section: Discussionmentioning
confidence: 99%
“…27 It is possible that with the onset of the COVID-19 pandemic its stay at home restrictions and business, closures that followed, many university students lost their part-time jobs and consequently experienced a decline in their income. 18,28 Analyzing data from the Japanese Labour Force Survey, Tsurugano et al, 28 found that the number of working students fell by 46% between April 2019 and April 2020. A study from Germany posits that students’ job income declined by 66%.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Minimally and maximally adjusted models showed a 35% higher prevalence of depressive symptoms in students who lost economic resources compared to students with stable economic resources during the lockdown. No substantial differences in the association between students' financial loss and depressive symptoms were found across countries (Tancredi et al, 2022 ). International students often pay several times more in tuition than local students to complete their studies in the host country, which requires financial support from their families or the government.…”
Section: Subsections Relevant For the Subjectmentioning
confidence: 99%